Debating the Future of Work: The Perception and Reaction of the Spanish Workforce to Digitization and Automation Technologies - Rodriguez-Bustelo, Carolina; Batista-Foguet, Joan Manuel; Serlavós, Ricard (Frontiers in Psychology, 2020)
Given the significant changes that are expected in the nature of work as a consequence of rapid technological advances, it is crucial that society finds ways to maximize benefits while recognizing and mitigating related challenges. This article is intended to fill a current research gap in this context by examining how aware and prepared affected workers are for the challenges predicted by research. This information is crucial since expectation and preparation of the workforce will significantly influence society’s adaptability to the future. As a result of the article various significant relationships among workers’ characteristics and their attitude towards automation could be identified. The interviewed workers’ level of fear appears to have very little influence on preparation for automation-driven changes in the future while perceived opportunity significantly impacts this degree of preparation. Characteristics that additionally most influence the degree of preparatory steps taken by respondents are their level of education as well as work complexity and position. These findings should be used to identify potential ways for relevant stakeholders to adequately prepare for and meet the challenges of the impending increase of automation in the workplace.